2015
DOI: 10.1002/mrm.25598
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis of hip joint cartilage combining MR T2 and three‐dimensional fast‐spin‐echo images

Abstract: The good agreement between the manual and automatic analyses of T2 values indicates the use of structural 3D-SPACE MR images with the proposed method provides a promising approach for automated quantitative T2 assessment of hip joint cartilages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…(Used with permission from (Chandra et al 2015b;Ho et al 2014) 6.3 Cartilage thickness measurement illustrated on an example 2D slice overlaid with manual cartilage contours. The example slice is assumed to go through the estimated center of the femoral head.…”
Section: Declaration By Authormentioning
confidence: 99%
See 4 more Smart Citations
“…(Used with permission from (Chandra et al 2015b;Ho et al 2014) 6.3 Cartilage thickness measurement illustrated on an example 2D slice overlaid with manual cartilage contours. The example slice is assumed to go through the estimated center of the femoral head.…”
Section: Declaration By Authormentioning
confidence: 99%
“…Li et al (2008) reported semi-automatic segmentation of the individual acetabular and femoral cartilage plates (using active contours) in 2D MEDIC MR images without the use of continuous leg traction. The use of these manual and semi-automatic approaches for cartilage segmentation typically requires skilled analysts with considerable experience and is time-consuming, e.g., 1 hour per image for semi-automatic analysis (Naish et al 2006) and 3 hours for manual delineation of the cartilages on each SPACE image (Chandra et al 2015b); consequently the development of an accurate automatic scheme for hip joint cartilage segmentation would be beneficial for large-scale clinical and research studies focusing on morphometric evaluations.…”
Section: Manual and Semi-automatic Segmentation Of Hip Joint Cartilagementioning
confidence: 99%
See 3 more Smart Citations